Women’s March Medan and the Resistance Against Gender-Based Violence: A Qualitative Study of Localized Feminist Activism - Intan Maulina; M. Manugeren; Efendi Barus (International Journal of Multidisciplinary Sciences and Arts, 2025)
Gender-based violence (GBV) remains one of Indonesia's most critical social issues, with thousands of cases reported annually and only a small proportion addressed legally. While global feminist movements like #MeToo and Ni Una Menos have been widely studied, there is limited research on localized feminist activism, particularly in regional contexts. This study explores the Women’s March Medan as a localized form of feminist resistance to GBV, aiming to understand how it raises awareness, builds solidarity, critiques structural inequalities, and navigates cultural and religious barriers. Using a qualitative descriptive approach, data were gathered through semi-structured interviews with six participants, document analysis, media reviews, and direct field observations. Thematic analysis identified five main themes: (1) elevating vulnerable groups and critiquing structural violence, (2) symbolic actions as political statements, (3) constructing awareness of GBV, (4) localization of global feminist discourses, and (5) reclaiming public space amidst backlash. The findings highlight that the Women’s March Medan is not a mere replication of international feminist models but a localized adaptation blending global solidarity with Indonesia’s socio-cultural and religious contexts. This study contributes to feminist scholarship by demonstrating how grassroots activism in Medan transforms mourning into protest, negotiates legitimacy within cultural and religious frameworks, and asserts feminist presence in contested public spaces. It also offers insights into how local feminist movements adapt global discourses to respond to GBV in distinct socio-political environments.